PERITONITIS IN NEWBORNS: SYMPTOMS OF THE DISEASE, METHODS OF DIAGNOSIS AND TREATMENT (World Bulletin of Public Health, 2022)
Peritonitis is a severe inflammatory disease that affects the inner wall of the abdominal cavity. In children, it progresses faster than in adults, and often turns into common forms and provokes the appearance of complications. In the absence of proper treatment, after three days it can lead to the development of sepsis. Peritonitis is an inflammation of the peritoneum, the tissue that lines the inner wall of the abdomen and covers and supports most of your abdominal organs. Peritonitis is usually caused by infection from bacteria or fungi.
Keywords: Peritonitis; Children; Newborn; Type Of Treatments.